2011
DOI: 10.1186/1752-153x-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of Greek pollen - Antioxidant, antimicrobial and proteasome activation properties

Abstract: BackgroundPollen is a bee-product known for its medical properties from ancient times. In our days is increasingly used as health food supplement and especially as a tonic primarily with appeal to the elderly to ameliorate the effects of ageing. In order to evaluate the chemical composition and the biological activity of Greek pollen which has never been studied before, one sample with identified botanical origin from sixteen different common plant taxa of Greece has been evaluated.ResultsThree different extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 31 publications
7
108
1
7
Order By: Relevance
“…The antioxidant activity seemed to be related to the total phenol content of the extract. Similar phenomena have been reported for propolis from Korea (Choi et al, 2006), Italian bee products (Buratti et al, 2007), Czech honey (Lachman et al, 2010), Brazilian honey (Sant'ana et al, 2014), Portuguese bee pollen (Morais et al, 2011), Greek bee pollen (Graikou et al, 2011), and Thai propolis (Siripatrawan et al, 2013). Flavonoids and phenolic components played an important role in the free radical scavenging capacity of the extract (Graikou et al, 2011).…”
Section: Antioxidant Activitysupporting
confidence: 73%
See 3 more Smart Citations
“…The antioxidant activity seemed to be related to the total phenol content of the extract. Similar phenomena have been reported for propolis from Korea (Choi et al, 2006), Italian bee products (Buratti et al, 2007), Czech honey (Lachman et al, 2010), Brazilian honey (Sant'ana et al, 2014), Portuguese bee pollen (Morais et al, 2011), Greek bee pollen (Graikou et al, 2011), and Thai propolis (Siripatrawan et al, 2013). Flavonoids and phenolic components played an important role in the free radical scavenging capacity of the extract (Graikou et al, 2011).…”
Section: Antioxidant Activitysupporting
confidence: 73%
“…Furthermore, the gram-negative bacteria possess a higher lipid amount than that observed in gram-positive bacteria (Morais et al, 2011).This lipid is a component of an endotoxin, which has responsible toxicity in the cell wall of gram-negative bacteria. Graikou et al (2011) reported that the MIC values of a Greek pollen-methanol extract were 0.74 and >10 mg/mL against S. aureus and E. coli, respectively. Morais et al (2011) found that the honeybee-collected pollen from Portuguese Natural Parks provided the MIC of 0.17% (w/v) for B. cereus, 0.21% (w/v) for S. aureus, and <5% (w/v) for E. coli.…”
Section: Antimicrobial Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Three different extracts of Greek pollen have been tested in whether could induce proteasome activities in human fibroblasts. The water extract of pollen was found to induce a highly proteasome activity (Graikou et al, 2011) showing interesting antioxidant effect because of flavonoids and phenolic acids, which indicate the observed free radical scavenging activity (Carpes et al, 2009). …”
Section: Electrophoretic Separation Of Po1len Pellets Proteinsmentioning
confidence: 99%